Comparison of the Effectiveness of Group Counseling Using Mindfulness-Based Cognitive Therapy and Acceptance and Commitment Therapy on Self-Compassion in Mothers - Fatahi, Mahmoud; Vaisi, Asadollah; Moradi, Omid (Psychology of Woman Journal, 2024)
Objective: This study aimed to compare the effectiveness of group counseling using Acceptance and Commitment Therapy (ACT) and Mindfulness-Based Cognitive Therapy (MBCT) on self-compassion among mothers of educable children. Methods and Materials: This research was a quasi-experimental study with a control group, utilizing a pre-test and post-test design with a control group and a 5-month follow-up period. The sampling method was simple random sampling. The statistical population consisted of 407 mothers of educable exceptional students, from which 36 participants were selected using random numbers and divided into three groups. The Self-Compassion Scale (Neff, 2003) was used as the assessment tool. Data analysis was conducted using covariance analysis to compare the means. SPSS software (version 22) was used for data analysis. Findings: The results showed that Acceptance and Commitment Therapy and Mindfulness-Based Cognitive Therapy had an impact of 59.6% and 27.9%, respectively, on increasing self-compassion compared to the control group (F = 106.891, P < 0.001). Conclusion: In conclusion, the study demonstrated that both Acceptance and Commitment Therapy (ACT) and Mindfulness-Based Cognitive Therapy (MBCT) effectively increase self-compassion in mothers of educable children, with ACT showing a greater impact. These findings highlight the potential of ACT and MBCT as effective interventions for enhancing psychological well-being in this population.